Hypofractionated versus conventionally fractionated radiotherapy for patients with prostate cancer (HYPRO): late toxicity results from a randomised, non-inferiority, phase 3 trial. Issue 4 (April 2016) - Aluwini, Shafak; Pos, Floris; Schimmel, Erik; Krol, Stijn; van der Toorn, Peter Paul; de Jager, Hanja; Alemayehu, Wendimagegn Ghidey; Heemsbergen, Wilma; Heijmen, Ben; Incrocci, Luca
Summary: Background: Several studies have reported a low α to β ratio for prostate cancer, suggesting that hypofractionation could enhance the biological tumour dose without increasing genitourinary and gastrointestinal toxicity. We tested this theory in the phase 3 HYPRO trial for patients with intermediate-risk and high-risk prostate cancer. We have previously reported acute incidence of genitourinary and gastrointestinal toxicity; here we report data for late genitourinary and gastrointestinal toxicity. Methods: In this randomised non-inferiority phase 3 trial, done in seven radiotherapy centres in the Netherlands, we enrolled intermediate-risk or high-risk patients aged between 44 and 85 years with histologically confirmed stage T1b–T4 NX–0MX–0 prostate cancer, a prostate-specific antigen concentration of 60 ng/mL or lower, and WHO performance status of 0–2. A web-based application was used to randomly assign (1:1) patients to receive either standard fractionation with 39 fractions of 2 Gy in 8 weeks (five fractions per week) or hypofractionation with 19 fractions of 3·4 Gy in 6·5 weeks (three fractions per week). Randomisation was done with the minimisation procedure, stratified by treatment centre and risk group. The primary endpoint was to detect a 10% enhancement in 5-year relapse-free survival with hypofractionation. A key additional endpoint was non-inferiority of hypofractionation in cumulative incidence of grade 2 or worse acute and late genitourinary and gastrointestinal toxicity. We planned to reject inferiority of hypofractionation for late genitourinary toxicity if the estimated hazard ratio (HR) was less than 1·11 and for gastrointestinal toxicity was less than 1·13. We scored toxicity with the Radiation Therapy Oncology Group and European Organisation for Research and Treatment of Cancer (RTOG/EORTC) criteria from both physicians' records (clinical record form) and patients' self-assessment questionnaires. Analyses were done in the intention-to-treat population. Patient recruitment for the HYPRO trial was completed in 2010. The trial was registered with www.controlled-trials.com, number ISRCTN85138529. Findings: Between March 19, 2007, and Dec 3, 2010, 820 patients (410 in both groups) were randomly assigned. Analyses for late toxicity included 387 assessable patients in the standard fractionation group and 395 in the hypofractionation group. The median follow-up was 60 months (IQR 51·2–67·3). The database for all analyses (both groups and both genitourinary and gastrointestinal toxicities) was locked on March 26, 2015. The incidence of grade 2 or worse genitourinary toxicity at 3 years was 39·0% (95% CI 34·2–44·1) in the standard fractionation group and 41·3% (36·6–46·4) in the hypofractionation group. The estimated HR for the cumulative incidence of grade 2 or worse late genitourinary toxicity was 1·16 (90% CI 0·98–1·38), suggesting that non-inferiority could not be shown. The incidence of grade 2 or worse gastrointestinal toxicity at 3 years was 17·7% (14·1–21·9) in standard fractionation and 21·9% (18·1–26·4) hypofractionation. With an estimated HR of 1·19 (90% CI 0·93–1·52) for the cumulative incidence of grade 2 or worse late gastrointestinal toxicity, we could not confirm non-inferiority of hypofractionation for cumulative late gastrointestinal toxicity. Cumulative grade 3 or worse late genitourinary toxicity was significantly higher in the hypofractionation group than in the standard fractionation group (19·0% [95% CI 15·2–23·2] vs 12·9% [9·7–16·7], respectively; p=0·021), but there was no significant difference between cumulative grade 3 or worse late gastrointestinal toxicity (2·6% [95% CI 1·2–4·7]) in the standard fractionation group and 3·3% [1·7–5·6] in the hypofractionation group; p=0·55). Interpretation: Our data could not confirm that hypofractionation was non-inferior for cumulative late genitourinary and gastrointestinal toxicity compared with standard fractionation. Before final conclusions can be made about the utility of hypofractionation, efficacy outcomes need to be reported. Funding: The Dutch Cancer Society.